2015
DOI: 10.1038/gene.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autoimmunity by CD5+ IL-10-producing B cells in lupus-prone mice

Abstract: Systemic lupus erythematosus is a complex autoimmune disorder characterized by the production of pathogenic anti-nuclear antibodies. Previous work from our laboratory has shown that the introgression of a New Zealand Black-derived chromosome 4 interval onto a lupus-prone background suppresses the disease. Interestingly, the same genetic interval promoted the expansion of both Natural Killer T- and CD5(+) B cells in suppressed mice. In this study, we show that ablation of NKT cells with a CD1d knockout had no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…We have previously shown that crossing the full-length (32 to 151 Mb) NZB c4 interval onto the lupus-prone B6.NZBc1 background leads to suppression of autoantibody production and renal disease, and have provided evidence through adoptive transfer experiments that this was mediated by a suppressive effect of NZB c4 CD5 + B cells [ 6 , 7 ]. This led us to hypothesize that the suppression was the result of the expansion of CD5 + B cells in B6.NZBc4 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that crossing the full-length (32 to 151 Mb) NZB c4 interval onto the lupus-prone B6.NZBc1 background leads to suppression of autoantibody production and renal disease, and have provided evidence through adoptive transfer experiments that this was mediated by a suppressive effect of NZB c4 CD5 + B cells [ 6 , 7 ]. This led us to hypothesize that the suppression was the result of the expansion of CD5 + B cells in B6.NZBc4 mice.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent follow-up publication, we investigated the immune mechanism leading to this suppression and ruled out a regulatory role for the expanded NKT cell population by creating CD1d knockout B6.NZBc1c4 bicongenic mice. Instead, a possible regulatory role for the expanded splenic CD5 + B cell compartment was identified [ 7 ]. Given the recent interest in regulatory B cells, we hypothesized that IL-10 production by CD5 + B cells was critical to suppression in our lupus-prone mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, systemic IL-10 administration has proven to be of limited value 120 and this indicates that IL-10 production would need to be carefully targeted to be efficacious therapeutically. This is evidenced by adoptive transfers of specific types of IL-10-producing immune cells in some autoimmune disease models that result in protection against the development of inflammatory pathologies 121 127 . Thus, a far more comprehensive and precise understanding of which IL-10-producing cells are important in vivo , and what the critical target cells of this IL-10 are would be instrumental in the future development of the therapeutic potentials of IL-10.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It should be noted that, in addition to MZB cells, increased numbers of B1 cells are noted in the salivary glands of IL-14α transgenic mice. B1 cells can generate B10 cells that produce IL-10 and these cells are known to inhibit inflammation in autoimmune disease [66,67,68,69]. …”
Section: Potential Roles For B Cells In Sjogren’s Syndromementioning
confidence: 99%